PERTANGGUNGJAWABAN WARGA NEGARA ASING (WNA) TERKAIT PENGGUNAAN KENDARAAN RENTAL YANG TERKENA TILANG ELEKTRONIK DI BADUNG (STUDI DI CV. BALI MUTIA RENTAL) - Arinanda Kusuma, Anak Agung Ngurah; Wiryawan, I Wayan Gde (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
ETLE is an electronic system of supervision and law enforcement for motorists in traffic. The application of Electronic Traffic Law Enforcement (ETLE) that occurs is very disadvantage to the community, especially rental business owners, where the violator is the renters of the vehicle, while the one who is obliged to pay or be responsible is the owner of the vehicle. Foreigners as renters should provide responsibility in the event of an electronic ticket violation. The research method used is empirical legal research, namely, where the law is conceptualised as real behaviour based on unwritten social symptoms. In this case, the researcher examines the renter and the vehicle rental business from a legal perspective, while data collection is carried out through observation, interview, and documentation techniques. The author concludes that foreigners as tenants have not been fully responsible for the rental party due to factors and the non-optimal implementation of ETLE.